The Influence of Diabetes on Acute Achilles Tendon Rupture Repair - Jonathan Kaplan MD; Jeffery Hillam BS; Amiethab Aiyer MD; Niall Smyth MD (Foot & Ankle Orthopaedics, 2018)
Category: Sports Introduction/Purpose: Diabetes Mellitus (DM) is an epidemic affecting millions of individuals in the United States. Multiple studies have demonstrated an increase in complications in foot and ankle surgery in patients with DM, including wound healing complications, surgical site infections (SSI), or surgical failure. The goal of this study was to retrospectively review outcomes data from the National Surgical Quality Improvement Program (NSQIP) to determine the impact of DM on operative treatment of achilles tendon ruptures. Methods: Using the NSQIP from 2006-2015, patients were identified using common procedure terminology (CPT) for Achilles tendon ruptures. Diabetic and non-diabetic cohorts were evaluated to compare demographics, comorbidities, perioperative details and 30-day outcomes. Statistical evaluation included a power analysis for the primary outcome measure of wound disruption as well as univariate analysis was performed using chi-squared or Fisher’s exact and Wilcoxon signed-rank tests. Results: A total of 2,014 patients were identified having sustained an Achilles tendon rupture. There were 1,981 patients without DM and 33 patients with DM. There were no significant differences in postoperative complications, including SSI, medical complications, and 30-day outcomes between patients with DM and non-DM patients undergoing surgical repair of acute Achilles tendon ruptures. The power analysis for wound disruption showed a P=0.9 with an alpha of 0.05, sample size of n=2014, and Pearson correlation coefficient of r=0.0721 Conclusion: While DM has been shown to have an increase in complications in various foot and ankle procedures, this study demonstrates that there is no significant difference in postoperative complications and 30-day outcomes between patients with DM and non-DM patients undergoing surgical repair of acute Achilles tendon ruptures using the NSQIP database from 2006-2015. Based on this data, patients with diabetes mellitus can be considered adequate surgical candidates for acute Achilles tendon rupture repair.